KARAKTERISTIK KANDUNGAN KIMIA DAN DAYA CERNA TEMPE SORGUM COKLAT (Sorghum bicolor) [Characteristics of Chemical Content and Digestibility of Brown Sorghum Tempeh] - Erni D.Sofia Murtini; Aji Sutrisno; Arfat Gati Radite (Jurnal Teknologi dan Industri Pangan, 2011)
Brown sorghum (Sorghum bicolor) is rarely used for food product because its protein has lower digestibility compared to other cereals. One factor affecting lower sorghum protein digestibility is anti nutritional effect from tannin and phytic acid. Some processing methods of sorghum have successfully increased protein digestibility, one of them is tempeh fermentation. The aims of this research were to degrade anti nutritional compounds and to increase in vitro protein digestibility of sorghum grain using tempeh fermentation. This research was performed in two steps; preparation of sorghum grain and production of sorghum tempeh. Proximate contents, anti nutritional compounds, and in vitro protein digestibility were tested. The test was applied to each of sorghum tempeh samples every 12 hour until 72 hours of total incubation time. The result of study showed that fermentation process decreased anti nutritional factors such as tannin and phytic acid, and increased in vitro protein digestibility of sorghum grain. The reduction of anti nutritions and increase of in vitro protein digestibility of sorghum grain were time-dependent in the fermentation process. The highest in vitro protein digestibility (79.13 %) was observed from 72 hour-fermented sorghum.